THE USE OF STEAM TECHNOLOGY FOR THE DEVELOPMENT OF APPLIED PHYSICS TEACHING - Usembayeva И.Б.; Ramankulov Ш.Ж.; Bitibaeva Ж.М.; Moldabekova М.С.; Polatuly1 С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
An urgent problem is the introduction of elements of applied orientation as one of the traditional directions in teaching, taking into account the relationship of physics with everyday life, in the field of industry, technology, engineering. The main purpose and idea of the research work: teaching students the discipline "electricity and magnetism " in the conditions of increasing the applied orientation based on STEAM – not only mastering a number of theoretical materials, but also ensuring the formation of skills for the independent application of the acquired knowledge in everyday life, in the fields of engineering, technology. The conscious assimilation of knowledge on the discipline based on STEAM allows you to apply them in a variety of situations. In the course of the study, its definition was proposed as a result of a review of the scientific literature in the field of applied physics education based on STEAM. A functional and structural model of the methodology for implementing the development of the applied orientation of teaching future physics teachers on the example of the subject "electricity and magnetism" has been developed.